Responsive pedagogy for multi-lingual classroom (Sotang, Yearly Peer Reviewed Journal, 2020)
In this paper I explore the concept of diversity in the classroom. Diversity means difference in terms of race, language, age, faith, culture, ethnicity, and in other aspects. Nepal is a multicultural and   multi lingual country. Where more than 123 languages are spoken. Such as Nepali, Maithili, Bhojpuri, Tharu, Newari, Abadhi etc National language is Nepali in Nepal. Social structure is also different from society to society. There are racially different people. The main are   Bramhin, Chhettri, Rai, Gurung,Tamang, Magar, Tharu, Newar and others who caste live here. There are mainly ten types of religious categories reported in the census 2011 A. D. The large number of people are followed by Hindu. Whereas Hinduism is followed by (81.3%), Buddhism (9%), Islam (4.4%) and so on. Nepal has been diversified in terms of ethnicity, religion, traditions and culture. People respect the national feeling of unity in diversity. Nepal is multi-cultural, multi-ethnic and multi-lingual society so there are diversity in the classroom. In this paper I explore the diversity in the classroom and students' achievement. In this paper I have introduced multicultural education, cultural responsive pedagogy and student achievement. The conclusion of this study is responsive pedagogy address and support to the student's achievement in diverse classroom.